Development of a User Interface for the Enrichment of Situational Awareness in Emergency Management Systems - Oliveira, Natalia (2016)
The individual's perception and understanding obtainment on events that transform an environment and their real critical contexts, is named Situational Awareness (SA). This process assists emergency management situation, allowing experts on SA acquisition and maintenance process, and provide subsidies for an assertive decision making. Specialized SA User Interfaces (UI) may facilitate the knowledge acquisition, allowing the perception and dynamic comprehension. The UIs design of SA-oriented systems in critical scenarios, as emergency management is a challenging issue, considering the presence of multiple heterogeneous data source, the information about situation that's in constant transformation and quality limitations associated every new inference. Known approaches seek to present specifically solutions to their application domain and are inevitably limited as the described needs in this paper. This paper presents the UI development to promote the visualization and situational information evolution follow-up, information quality aware, driven to a case of study in emergency management, which includes new challenges like the data presentation from human intelligence.